Dissolved organic carbon in thermokarst lakes - Stolpmann, Lydia (Dr.) (2025)
The Arctic is warming faster compared to other regions on Earth, resulting in significant permafrost thaw, a process that causes the release of stored organic carbon into aquatic systems, particularly thermokarst lakes. These dynamic systems, formed by the degradation of ice-rich permafrost, play an important role in the global carbon cycle. Dissolved organic carbon (DOC), a major carbon fraction in thermokarst lakes, can either be sequestered in lakes sediments or degraded through microbial and photochemical processes and further released into the atmosphere as carbon dioxide (CO2) and methane (CH4), two potent greenhouse gases. The knowledge on processes of DOC in thermokarst lakes is essential for predicting their impact on climate change. This thesis aims to address gaps in our understanding of DOC dynamics in Arctic thermokarst lakes. Therefore, the research objectives include: (1) identifying linkages between DOC concentrations and environmental characteristics on a pan- Arctic scale, (2) investigating landscape components in a yedoma catchment and their influence on DOC fluxes in surface waters, and (3) analyzing the impacts of lake changes on DOC concentrations at a regional scale. To achieve this, we combined data synthesis, field investigations, hydrochemical analysis, remote sensing, and geospatial analysis. We conducted measurements of DOC concentrations, electrical conductivity, pH, stable water isotopes, radiocarbon dating, and CH4 concentrations from thermokarst lakes of various size and lagoons to analyze DOC sources, pathways, and transformations. Through our extensive dataset of 2,167 water samples from 1,830 lakes across Alaska, Canada, Greenland, and Siberia, we demonstrated significant regional variations in DOC concentrations. These variations are linked to latitude, permafrost extent, ecoregions, geology, and soil organic carbon content. In our detailed study of a small lake catchment in the Lena River Delta, we identified the degradation of old yedoma permafrost as a major DOC source. ...